Radionuclide distribution in soil and undecayed vegetative litter samples in a riparian system at the Savannah River Site, SC. (December 2018) - Wu, Chieh-Ming; Adetona, Olorunfemi; Naeher, Luke; Viner, Brian J.; Jannik, Tim; Hepworth, Allan; Doman, Eric; Eddy, Teresa
Abstract: The aim of this study is to comprehensively investigate radionuclide concentrations in surface soil and un-decayed vegetative litter along four stream systems (i.e. Fourmile Branch, Lower Three Runs, Pen Branch, and Steel Creek) at the Savannah River Site (SRS), Aiken, South Carolina. Soil and litter samples from systematically spaced 12 pairs (contaminated or uncontaminated) of plots along the four streams were analyzed for 16 distinct radionuclide activities. Lower radionuclide concentrations were observed in soil and litter samples collected along Pen Branch compared to the other 3 streams. The anthropogenic radionuclide with the highest activity was 137 Cs in soil (10.6–916.9 Bq/kg) and litter (8.0–222.3 Bq/kg), while the naturally occurring radionuclides possessing the highest concentration in the samples were 40 K (33.5–153.7 Bq/kg and 23.1–56.0 Bq/kg in soil and litter respectively) and 226 Ra (55.6–159.9 Bq/kg and 30.2–101.8 Bq/kg in soil and litter respectively). A significant difference (p < 0.05) of radionuclide concentrations between paired-plots across four streams was observed for 241 Am, 137 Cs, 238 Pu, 239 Pu, and 226 Ra in both contaminated and non-contaminated samples. 137 Cs and uranium isotopes had the highest litter-to-soil correlation in contaminated (rho = 0.70) and uncontaminated plots (rho = 0.31–0.41), respectively. 90 Sr was the only radionuclide with higher radioactive concentrations in litter (12.65–37.56 Bq/kg) compared to soil (1.61–4.79 Bq/kg). The result indicates that 1) historical discharges of anthropogenic 137 Cs was the most important contributor of radiation contamination in the riparian environment at SRS, 2) 90 Sr was the only radionuclide with higher concentration in litter than in soil, and 3) no apparent pattern in deposition density in soil or litter along downstream was observed for the radionuclides measured in this study. Highlights: The distribution of radionuclides in contaminated and uncontaminated plots along a riparian system was characterized. 137 Cs, 226 Ra, and 40 K were the radionuclides with the highest activity in the soil and litter along the streams. 90 Sr was the only radionuclide with a higher radioactivity in the litter than in the soil. Correlation between soil and litter was observed for 137 Cs in contaminated plots and U isotopes in uncontaminated plots. No apparent spatial trend in deposition density of the radionuclides along the streams was observed.